2004
DOI: 10.2135/cropsci2004.4180
|View full text |Cite|
|
Sign up to set email alerts
|

Identification and Characterization of a Low Phytic Acid Wheat

Abstract: Phytic acid (myo‐inositol‐1,2,3,4,5,6‐hexakisphosphate, or Ins P6) is the most abundant storage form of P in seeds, yet indigestible by humans and nonruminant livestock. A wheat (Triticum aestivum L.) mutant is described herein with greatly reduced seed phytic acid P but little change in seed total P, similar to lpa1‐type mutants described in other grain species. One nonlethal mutant from 562 ethyl‐methanesulfonate (EMS) mutagenized M2 lines was identified with a high inorganic phosphate (HIP) phenotype and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
129
2
9

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 166 publications
(145 citation statements)
references
References 22 publications
5
129
2
9
Order By: Relevance
“…Studies of germplasm collections have revealed significant genetic variation for both seed phytate and/or total P in common bean, lentil, sorghum, soybean, and wheat (Lolas and Markakis 1975;Raboy et al 1991;Israel et al 2006;Kayode et al 2006;Ficco et al 2009;Thavarajah et al 2010;Akond et al 2011). Likewise, researchers have used both chemical and physical mutagens to isolate lp mutants in barley (Raboy 2000;Bowen et al 2006), common bean (Campion et al 2009), maize (Raboy 2000;Badone et al 2010), rice (Larson et al 2000;Raboy 2000;Rutger et al 2004;Liu et al 2007;Kim et al 2008), soybean (Wilcox et al 2000;Walker et al 2006), and wheat (Guttieri et al 2004). These studies reported two types of mutants, those with moderate reduction (50%-65%) or extreme reduction (95%) in phytic acid, with the latter being homozygotes and lethal.…”
Section: Mining Germplasm Collections For Natural Variation For Sementioning
confidence: 99%
“…Studies of germplasm collections have revealed significant genetic variation for both seed phytate and/or total P in common bean, lentil, sorghum, soybean, and wheat (Lolas and Markakis 1975;Raboy et al 1991;Israel et al 2006;Kayode et al 2006;Ficco et al 2009;Thavarajah et al 2010;Akond et al 2011). Likewise, researchers have used both chemical and physical mutagens to isolate lp mutants in barley (Raboy 2000;Bowen et al 2006), common bean (Campion et al 2009), maize (Raboy 2000;Badone et al 2010), rice (Larson et al 2000;Raboy 2000;Rutger et al 2004;Liu et al 2007;Kim et al 2008), soybean (Wilcox et al 2000;Walker et al 2006), and wheat (Guttieri et al 2004). These studies reported two types of mutants, those with moderate reduction (50%-65%) or extreme reduction (95%) in phytic acid, with the latter being homozygotes and lethal.…”
Section: Mining Germplasm Collections For Natural Variation For Sementioning
confidence: 99%
“…Fitinska kiselina kao polivalentni anjon stvara helate sa mineralnim elementima i proteinima, onemogućavajući njihovo potpuno iskorišćavanje. Ishrana bogata fitinskom kiselinom značajno smanjuje apsorpciju važnih mikronutrijenata (kalcijum, cink, gvožđe, mangan i bakar) koje ljudi i nepreživari (živina, svinje, ribe) u vidu mešovitih soli izlučuju, dovodeći do njihovog ozbiljnog defi cita, naročito kod siromašnih i zemalja u razvoju (Reicwald & Hatzack 2008, Khan et al 2007, Guttieri et al 2004, Lönnerdal 2002, García-Estepa et al 1999, Tabekhia & Donelly 1982, Nahapetian & Bassiri 1976, Lolas et al 1976.…”
Section: Uvodunclassified
“…Obuhvata jedan do nekoliko procenata suve mase semena i 50% do 85% ukupnog fosfora u semenu pšenice (Raboy 2001a, Guttieri et al 2004, Hídvégi & Lásztity 2002, Khan et al 2007, Yenagi & Basarkar 2007, Dintzis et al 1992, Nahapetian & Basiri 1976. Količina fosfora sintetisana u formi InsP 6 predstavlja više od 50% unešenog fosfora u agroekosisteme mineralnim đubrenjem na godišnjem nivou.…”
Section: Fitinska Kiselina Kod Pšenice -Uloga I Fi Zička Pozicija U Sunclassified
See 2 more Smart Citations